2010
DOI: 10.1111/j.1556-4029.2010.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Approach to an Archaeological Casework of “Vampire” Skeletal Remains in Venice: Odontological and Anthropological Prospectus*

Abstract: During the years 2006-2007, the Archeological Superintendent of Veneto (Italy) promoted a research project on mass graves located on Nuovo Lazzaretto in Venice, where the corpses of plague deaths were buried during the 16th and 17th centuries. The burials were of different stages and are believed to be the remains of plague victims from the numerous outbreaks of pestilence, which occurred between the 15th and 17th centuries. Among the fragmented and commingled human bones, an unusual burial was found. The body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Indeed, there have been accounts, often in popular media, of comparable interments from a variety of medieval and postmedieval sites in Europe (see Table in Gregoricka et al () for a list of reported deviant burials associated with vampirism). In addition to coverage in news media outlets, published scientific investigations of such burials exist (Betsinger & Scott, ; Garas, ; Gregoricka et al, ; Jankowski & Kurasiński, ; Koperkiewicz, ; Matczak & Kozlowski, ; Nuzzolese & Borrini, ) but are less common. Matczak and Kozlowski () investigated an early medieval Polish cemetery site to determine whether there was an association of people with particular diseases or disabilities who had received anti‐vampiristic treatment (e.g., decapitation, prone body position, inclusion of large stones) upon their deaths, and found that individuals with pathological conditions such as tuberculosis were not more likely to receive such funerary treatments.…”
Section: Vampire Lore and Deviant Burialsmentioning
confidence: 99%
“…Indeed, there have been accounts, often in popular media, of comparable interments from a variety of medieval and postmedieval sites in Europe (see Table in Gregoricka et al () for a list of reported deviant burials associated with vampirism). In addition to coverage in news media outlets, published scientific investigations of such burials exist (Betsinger & Scott, ; Garas, ; Gregoricka et al, ; Jankowski & Kurasiński, ; Koperkiewicz, ; Matczak & Kozlowski, ; Nuzzolese & Borrini, ) but are less common. Matczak and Kozlowski () investigated an early medieval Polish cemetery site to determine whether there was an association of people with particular diseases or disabilities who had received anti‐vampiristic treatment (e.g., decapitation, prone body position, inclusion of large stones) upon their deaths, and found that individuals with pathological conditions such as tuberculosis were not more likely to receive such funerary treatments.…”
Section: Vampire Lore and Deviant Burialsmentioning
confidence: 99%
“…Although a year has elapsed since publication, we are writing this review concerning the paper ''Forensic approach to an archaeological casework of 'vampire' skeleton remains in Venice: odontological and anthropological prospectus,'' by Nuzzolese and Borrini (1). The reason for this reply is that in Italy the story of the ''Vampire of Venice'' is receiving extraordinary emphasis in the mass media, but despite the coverage given to the subject in journals, television, and a documentary by National Geographic, this is the only article published on the subject.…”
Section: Sirmentioning
confidence: 99%
“…The published image (Fig. 2 in Nuzzolese and Borrini paper [1]) shows a vertical brick, not touching the teeth, inside the mouth, and this seems to suggest that the brick had been inserted (or, simply, had accidentally fallen) after the jaw had assumed such a large opening, subsequent to the skeletonization of the body; otherwise the brick would have injured the teeth. Furthermore, a secondary infiltration of sediments into the mouth (after skeletonization) is suggested by the fact that the brick stands vertically, not leaning onto the teeth.…”
mentioning
confidence: 99%
“…In many occasions forensic departments have conducted analysis on remains with no medicolegal significance, collaborating in multidisciplinary projects involving human archaeological, anatomical and museological specimens [1][2][3][4][5][6][7][8] . During these types of investigations, forensic specialists have the possibility to develop protocols for forensic authentication of artefacts 1,3 , as well as retrieve information (e.g.…”
Section: Introductionmentioning
confidence: 99%